Determine Optimal Preventive Maintenance Time Using Scheduling Method - علوان, فارس مهدي; فاضل, غصون حربي (Journal of Economics and Administrative Sciences, 2018)
In this paper, the reliability and scheduling of maintenance of some medical devices were estimated by one variable, the time variable (failure times) on the assumption that the time variable for all devices has the same distribution as (Weibull distribution.The method of estimating the distribution parameters for each device was the OLS method.The main objective of this research is to determine the optimal time for preventive maintenance of medical devices. Two methods were adopted to estimate the optimal time of preventive maintenance. The first method depends on the maintenance schedule by relying on information on the cost of maintenance and the cost of stopping work and access to the optimum time for maintenance, which achieves the lowest costs. The second method depends on the reliability function, which was to determine the optimal maintenance period, which then cost less Can. We also proved through this research that the method of scheduling is better than the method of relying on the reliability function because it depends heavily on the cost of maintenance.